2002
DOI: 10.1590/s0074-02762002000500009
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of hepatitis C Virus infection among hemophiliacs in Central Brazil

Abstract: In order to investigate the hepatitis C virus (HCV) infection prevalence and risk factors in hemophiliacs in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
10
0
3

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 8 publications
3
10
0
3
Order By: Relevance
“…Prior to these developments, the HCV and HBV infection rates in hemophilic patients in Poland were high (95% of those who were anti-HCV positive, 8.7% of HBsAg, and 68% of anti-HBc positive) (2), whereas the rates observed in the general population were significantly lower (anti-HCV was 0.6% - 2.1% and HBsAg was about 1%) (15-19). Our results were comparable with the rates observed among hemophiliacs in the USA and Western European countries (3, 4, 10, 20). …”
Section: Discussionsupporting
confidence: 89%
“…Prior to these developments, the HCV and HBV infection rates in hemophilic patients in Poland were high (95% of those who were anti-HCV positive, 8.7% of HBsAg, and 68% of anti-HBc positive) (2), whereas the rates observed in the general population were significantly lower (anti-HCV was 0.6% - 2.1% and HBsAg was about 1%) (15-19). Our results were comparable with the rates observed among hemophiliacs in the USA and Western European countries (3, 4, 10, 20). …”
Section: Discussionsupporting
confidence: 89%
“…Other Iranian studies have reported the prevalence of HCV in hemophilia patients as follows: Ahvaz 54 % (Assarehzadegan et al 2012 (Alavian et al 2003), and Bushehr 41.9 % (Rezvan et al 2007). Furthermore, the anti-HCV prevalence in our study was lower than Pakistan (56 %) (Waheed et al 2009), India (23.9 %) (Ghosh et al 2000), Brazil (60 %) (Barbosa et al 2002), and some neighboring Arabic countries (66-79 %) (Bahakim et al 1991;Al-Kubaisy et al 2006). Similar study conducted on 367 hemophilia patients in Shiraz (1992Shiraz ( to 2002 was also reported 15 % HCV seropositivity (Karimi et al 2002).…”
Section: Discussionmentioning
confidence: 44%
“…In a previous study conducted on hemophiliac patients from Goiânia, subtype 1a (41%) was also dominant, followed by subtypes 1b (25.6%) and 3a (20.5%) (18). Among blood donors, subtype 1a (54.6%) was also the most frequent, but subtype 3a (31.8%) was detected more frequently than subtype 1b (9.1%) (19).…”
mentioning
confidence: 77%